Temperament: How music became a battleground for the great minds of Western civilization - Isacoff, Stuart M. (New York Vintage books, 2001)
Few music lovers realize that the arrangement of notes on today?s pianos was once regarded as a crime against God and nature, or that such legendary thinkers as Pythagoras, Plato, da Vinci, Galileo, Kepler, Descartes, Newton and Rousseau played a role in the controversy. Indeed, from the time of the Ancient Greeks through the eras of Renaissance scientists and Enlightenment philosophers, the relationship between the notes of the musical scale was seen as a key to the very nature of the universe.In this engaging and accessible account, Stuart Isacoff leads us through the battles over that scale, placing them in the context of quarrels in the worlds of art, philosophy, religion, politics and science. The contentious adoption of the modern tuning system known as equal temperament called into question beliefs that had lasted nearly two millenia?and also made possible the music of Beethoven, Schubert, Chopin, Debussy, and all who followed. Filled with original insights, fascinating anecdotes, and portraits of some of the greatest geniuses of all time, Temperament is that rare book that will delight the novice and expert alike.